The Relationship between Product Nature and Supply Chain Strategy; An empirical evidence - Salman Shabbir, Muhammad; Asad, Muzaffar; Faisal, Muhammad; Salman, Rabia (ExcelingTech, 2019)
Abstract The purpose of the paper is to explore the relationship between the nature of product and respective supply chain strategy of the firms operation in manufacturing sector. The relationship is investigated by using the fishers model as conceptual framework. Data was collected through questionnaire-based self-administered survey. The results of the survey were analysed by testing the fishers model related to Supply Chain Strategy and product characteristics. The results of the study indicated that there is a significant relationship between nature of the product and supply chain strategy in manufacturing sector of Pakistan. The practical implication can be derived by the policy makers and practitioners of the supply chain strategy domain that characteristics of the product can have an impact of the decision to device supply chain strategy. Furthermore, this study is conducted in special context of underdeveloped country like Pakistan. Therefore, results of this study enhanced the existing literature on underdeveloped economies.